Sinergitas Pemenuhan Kebutuhan Informasi Melalui Program Paperbuk di Perpustakaan Unisa Yogyakarta - Zeni Istiqomah; Layyina, Lilik; Rachmawati, Dita (Media Informasi, 2024)
The library and its patrons synergize to fulfill their respective functions and roles. At the forefront of information provision, the library has the task of providing information tailored to the needs of its patrons. This research aims to analyze the synergy the Unisa Yogyakarta Library conducted in meeting information needs through the "Paperbuk" program. The research method used is qualitative descriptive. Data collection techniques are conducted through observation, interviews, and documentation. The validity test is performed through source triangulation, which involves cross-checking information from various sources using the employed techniques. Data analysis is done by data reduction, presentation, and conclusion drawing. The research findings indicate that the combined library and book exhibition activities (Paperbuk) organized by the Unisa Yogyakarta Library positively impact the library and its patrons. Forms of patron synergy include patrons' choice of books according to their interests and needs, their special borrowing rights, and the library exhibition (posters), a source of pride for patrons. From the library's perspective, this activity serves as a promotional platform, aids in book selection and procurement, increases visits, and enhances patrons' reading interests.